Principal Leadership in the “Program Sekolah Penggerak” to Improve Teacher Performance - Fauzi, Ihwan; Maimun, Agus; Yasin, Ahmad Fatah (JURNAL AL-TANZIM, 2024)
This research investigates the changes school principals face in improving education quality through the Program Sekolah Penggerak in Indonesia. The principal's leadership is considered one of the key factors in successfully implementing this program. This study uses a qualitative approach by analyzing data from interviews, observations, and document analysis at SMAIT Miftahul Khoir Bandung. The results of the research show that school principals in this program are more active in directing (decision making, developing RKAS and budgeting, designing educational unit operational curricula, experience regarding curriculum changes, evaluative competence), managing human resources (building the personal capacity of teachers and staff, building a conducive culture, organizing the school structure), and building partnerships. With the various trainings available both through the direction of school principals and the government, it is hoped that teachers will become more active in capturing various changes in the curriculum and become role models for other schools. The research is expected to contribute to the researchers who will conduct military research on madrasa-based schools in implementing the independent curriculum.